Abatacept in the Treatment of Juvenile Dermatomyositis-Associated Calcifications in a 16-Year-Old Girl - Sukesh Sukumaran; Vini Vijayan (Case Reports in Rheumatology)
Calcinosis is a feared complication of JDM that may be seen in up to 40% of children with JDM. It is associated with negative impact on the patients’ quality of life due to weakness, functional disability, joint contractures, muscle atrophy, skin ulcers, and secondary infections. Calcinosis can present as superficial nodules or plaques, larger nodular deposits extending into deeper tissue layers, accumulation of calcifications along the fascial planes of muscles or tendons, or an exoskeleton of calcium leading to limitations in mobility and joint contractures. Currently, there are no known effective treatments for calcinosis and current therapy is based on anecdotal retrospective studies and cases series. We report the case of a child with JDM-associated calcinosis with extensive intramuscular calcifications who failed conventional therapies but demonstrated improvement as evident by decrease in calcinosis and improved physical function with use of abatacept. We found that use of abatacept was associated with improvement in functional outcome and recurrence did not occur. This case suggests use of abatacept as a safe and effective treatment option for calcinosis due to JDM. Furthermore, large-scale clinical studies are needed to validate our findings and to evaluate the long-term outcomes.